THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION, CREATIVITY AND SELF EFFICACY IN DEVELOPING ENTREPRENEURSHIP INTERESTS IN STUDENTS OF THE ENTREPRENEURSHIP STUDY PROGRAM, FACULTY OF ECONOMICS AND BUSINESS, MALIKUSSALEH UNIVERSITY - Yusmalina; Samsidar; Agustinawati; M. Subhan (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the influence of entrepreneurship education, creativity, and self-efficacy on entrepreneurial interest among students in the Entrepreneurship Study Program at the Faculty of Economics and Business, Malikussaleh University. The research background is based on the low number of entrepreneurs in Indonesia and the high rate of educated unemployment, which encourages the need to cultivate an entrepreneurial spirit from the start of study. The research method used was quantitative descriptive-verification, with a population of 138 active students. Data analysis techniques included multiple linear regression and other statistical tests. The results indicate that entrepreneurship education, creativity, and self-efficacy have a positive and significant effect on entrepreneurial interest, both partially and simultaneously. These findings reinforce the importance of formal education and psychological factors in shaping entrepreneurial interest among students and recommend the integration of practical approaches and character development into the entrepreneurship learning process to produce graduates who are ready to become entrepreneurs.